THE SIGNS OF THE ‘DEMISE’ OF INDONESIAN LAW - Sumaryati, SH (Jurnal IUS Kajian Hukum dan Keadilan, 2013)
One of the purpose of the formulation and enactment of laws in Indonesian is to create of a peaceful, comfortable, orderly, and fair. Basically the purpose of the law can be approached from the essence of law . The essence of law or rules is to protect the rights of the community, and provide opportunities “more “ to the public . Thus the people who obey the law, their rights as citizens are protected and realized, as well as having the opportunity to be compared with other community members. Example, if the other party is not known, then the corruption, cheating can be done. If there is no police, the traffic violation can be done. As one consequence legal purposes not materialized in public life. Justice is still a very high value, well-being has not been felt by the majority of society , feeling comfortable, peaceful, and orderly atmosphere that is missed by the people. That there are signs of not implemented of rule or law. The signs of not implemented law, can be expressed as a sign of “ legal death “, in the sense that the law does not function in accordance with the function, role, and purpose . The application of the law in the reality of people’s lives , still formalistic, have not enactments expressly sanction yet, the judicial mafia. Those are phenomenal the “ death “ of law in the country of Indonesia.Keywords : Nature of law, causality of law, existence of legal, law enforcement